THE EFFECTS OF AN ARTIFICIAL COMMERCIAL FEED SUPPLEMENTATION ON LARVAL REARING AND CRABLET PRODUCTION OF MUD CRAB Scylla tranquebarica - Gunarto Gunarto; Muhammad Nur Syafaat; Herlinah Herlinah; Sulaeman Sulaeman; Muliani Muliani (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2018)
The effects of an artificial commercial feed supplementation on larval rearing and crablet production of mud crab Scylla tranquebarica. In mass production of mud crab seeds, only rotifer and Artemia nauplii are usually fed to mud crab larvae rearing until the larvae develop to crablet stage. The supplementation of artificial commercial feed from zoea-3 stage is expected to supply an essential nutrient required for an optimum larval development. The research was aimed to determine the optimum dosage of commercial feed supplementation for a successful larval rearing to produce crablet in hatchery. Newly hatched larvae of mud crab were stocked at a density of 100 ind./L. The larvae were fed with rotifer and Artemia nauplii. Microbound artificial commercial feed sized <100 microns (protein 52%, fat 14,5%, fiber 3% and water content 10%) was supplemented to the larvae from zoea-3 to megalopa stage at different dosages namely: a). 0.5 mg/L/2 days; b). 0.75 mg/L/2 days; c). 1.0 mg/L/2 days; d). 1.25 mg/L/2 days. Larval population, larval development indices (LDI), megalopa occurrence index (MOI) and crablet production were observed and measured. Water quality (ammonium, nitrite, Total Organic Matter (TOM), and total Vibrio sp. count were also monitored. The LDI, MOI, and crablet production from each treatment were compared and tested using one way-ANOVA. The results showed that the survival rate of larvae at zoea-5 ranged between 29-33%. The LDI was not significantly different (P>0.05) among treatments. However, the MOI of treatment A and B at day 21 ph was significantly higher (P<0.05) compared with treatment C and D. In addition, the crablet production in treatment B, C and D were significantly higher (P<0.05) compared with treatment A. It was concluded that the supplementation of artificial commercial feed in larval rearing of S. tranquebarica could be applied at the dosage range of 0.75-1.25 mg/L/2-days from zoea-3 until crablet (C-7) stage.